Digestive perforations related to endoscopy procedures: a local management charter based on local evidence and experts’ opinion - Bertrand, Gaspard; Rivory, Jérôme; Robert, Maud; Saurin, Jean-Christophe; Pelascini, Élise; Monneuse, Olivier; Gruner, Laurent; Poncet, Gilles; Valette, Pierre-Jean; Gimonet, Hélène; Rostain, Florian; Ber, Charles-Éric; Bouffard, Yves; Boibieux, André; Ciochina, Marina; Landel, Verena; Boyer, Hélène; Jacques, Jérémie; Ponchon, Thierry; Pioche, Mathieu (Endoscopy International Open, 2022)
Background and study aims Perforations are a known adverse event of endoscopy procedures; a proposal for appropriate management should be available in each center as recommended by the European Society of Gastrointestinal Endoscopy. The objective of this study was to establish a charter for the management of endoscopic perforations, based on local evidence. Patients and methods Patients were included if they experienced partial or complete perforation during an endoscopic procedure between 2008 and 2018 (retrospectively until 2016, then prospectively). Perforations (size, location, closure) and management (imagery, antibiotics, surgery) were analyzed. Using these results, a panel of experts was asked to propose a consensual management charter. Results A total of 105 patients were included. Perforations occurred mainly during therapeutic procedures (91, 86.7%). Of the perforations, 78 (74.3 %) were diagnosed immediately and managed during the procedure; 69 of 78 (88.5 %) were successfully closed. Closures were more effective during therapeutic procedures (60 of 66, 90.9 %) than during diagnostic procedures (9 of 12, 75.0 %, P = 0.06). Endoscopic closure was effective for 37 of 38 perforations (97.4 %) < 0.5 cm, and for 26 of 34 perforations (76.5 %) ≥ 0.5 cm (P < 0.05). For perforations < 0.5 cm, systematic computed tomography (CT) scan, antibiotics, or surgical evaluation did not improve the outcome. Four of 105 deaths (3.8 %) occurred after perforation, one of which was attributable to the perforation itself.Conclusions Detection and closure of perforations during endoscopic procedure had a better outcome compared to delayed perforations; perforations < 0.5 cm had a very good prognosis and CT scan, surgeon evaluation, or antibiotics are probably not necessary when the endoscopic closure is confidently performed. This work led to proposal of a local management charter.